Informatization and digitalization of teacher education: problems and prospects of development - Oksana V. Kitikar (RUDN Journal of Informatization in Education, 2023)
Problem statement . Modern teacher education is designed to meet the needs of the state and the requests of society related to the global information and digital transformation. This strengthens the tendency to modernize the system of teacher training at the state, regional, local and subject levels. Based on the analysis of the concepts of “digitalization”, “informatization”, “pedagogical education”, “pedagogical activity”, the filling of the parameters of digital education, depending on its functions to ensure the quality of pedagogical education at all levels is determined. The interconnection and interdependence of the components of the digital educational environment and the structural and functional constructs of teacher education are considered. Methodology. The definition of problems and prospects for the development of informatization and digitalization of teacher education is based on a terminological and content-functional analysis of the concepts of digitalization and informatization of education, the digital educational environment. A structural and functional analysis of the positive domestic experience in the formation of information and digital educational environments in the universities of the Russia was carried out. The criteria for the directions of development of informatization and digitalization of teacher education was specified, based on the requirements of the state reflected in regulatory documents, the requests of regions, determined on the basis of an analysis of strategies for their development, modernization of the structure, content and requirements for training at the institutional level. Results. The theoretical aspects of the conjugation of the terms of informatization and digitalization, influencing the modernization of the sphere of teacher training, have been identified and substantiated. The problems of the system of teacher education are considered, which indicate the need for its reform on the basis of intensification of information and digital transformation of this sphere. Conclusion. The requirements and directions of modernization of teacher education in the conditions of digital transformation, which are associated with a change in approaches to the training of teachers, to the need for integrative consideration of the functions of pedagogical activity and the digital educational environment are defined.